PERAN MAHKAMAH KONSTITUSI DALAM PENEGAKAN HAK ASASI MANUSIA - Arga Baskara; Febri Atikawati Wiseno Putri (Bajang Institute, 2025)
This study aims to analyse the strategic role of the Constitutional Court (MK) in the enforcement of human rights (HAM) in Indonesia. Using a literature review method and a normative legal approach, this study positions the MK as a key actor in the constitutional mechanism for protecting human rights. The MK's authority to review laws against the 1945 Constitution of the Republic of Indonesia makes it an important instrument in upholding the principles of justice and equality before the law. Several MK rulings have demonstrated its commitment to human rights values, particularly through the invalidation of discriminatory legal norms and the strengthening of citizens' constitutional rights. However, the MK's vital role still faces challenges, especially in the implementation of rulings, which are often not optimally responded to by executive and legislative institutions. This indicates a gap between the judicial and political spheres in efforts to comprehensively enforce human rights. Thus, this study affirms that the Constitutional Court not only acts as the last bastion of human rights protection, but also as a driving force for national legal reform to be more responsive to human rights values and principles. Going forward, synergy between state institutions is key to strengthening the effectiveness of the Constitutional Court in guaranteeing respect for and protection of human rights in Indonesia